1993
DOI: 10.1091/mbc.4.3.293
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular free Ca2+ in the cell cycle in human fibroblasts: transitions between G1 and G0 and progression into S phase.

Abstract: Intracellular free calcium ([Ca2+]i) has been proposed to play an important part in the regulation of the cell cycle. Although a number of studies have shown that stimulation of quiescent cells with growth factors causes an immediate rise in [Ca21]i (Rabinovitch et al., 1986;Vincentini and Villereal, 1986;Hesketh et al., 1988;Tucker et al., 1989;Wahl et al., 1990) This study is the first to show a direct relationship between early serum stimulated Cai2+ increase and subsequent DNA synthesis in human cells. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 28 publications
1
24
0
1
Order By: Relevance
“…Chelating external Ca 2ϩ by EGTA prevents substance P-induced proliferation of cultured rat cardiac fibroblasts (43). In human fibroblasts, it has been reported that Ca 2ϩ influx is essential for the proliferation, and intracellular Ca 2ϩ is required for cell cycle progression from G1/G0 to S phase (64). We have recently shown that human cardiac fibroblasts contain several TRPC-mediated Ca 2ϩ influx pathways, and TGF-␤ 1 enhances the Ca 2ϩ influx pathways requiring Ca 2ϩ signals for its effect on fibroblast proliferation (35).…”
Section: Discussionmentioning
confidence: 99%
“…Chelating external Ca 2ϩ by EGTA prevents substance P-induced proliferation of cultured rat cardiac fibroblasts (43). In human fibroblasts, it has been reported that Ca 2ϩ influx is essential for the proliferation, and intracellular Ca 2ϩ is required for cell cycle progression from G1/G0 to S phase (64). We have recently shown that human cardiac fibroblasts contain several TRPC-mediated Ca 2ϩ influx pathways, and TGF-␤ 1 enhances the Ca 2ϩ influx pathways requiring Ca 2ϩ signals for its effect on fibroblast proliferation (35).…”
Section: Discussionmentioning
confidence: 99%
“…This incomplete inhibition of fibroblast proliferation suggest that calcyclin plays a role in modulating the intracellular signaling events necessary for cells to divide. Thus, calcyclin could potentially play a role in calcium homeostasis and signaling of intracellular calcium transients required at various control points of the cell cycle in mitogen stimulated cells [Wahl and Gruenstein, 1993]. Likewise, pulmonary fibroblasts respond to strain with an increase in intracellular calcium levels via gadolinium sensitive calcium channels and release of the mitogen, PDGF.…”
Section: Calcyclin Attenuates Pulmonary Fibroblast Proliferationmentioning
confidence: 99%
“…Mitogenic stimulation of PLC␥ leads to a rapid and transient increase of intracellular calcium through the second messenger inositol triphosphate (31), as well as the generation of diacyl glycerol (DAG) with subsequent activation of PKC (32). Although the role of this calcium "spike" in mitogenesis is poorly character-ized (31,33,34), increases in calcium and DAG result in activation of both the conventional and novel PKCs. Although simultaneous activation of PI3K I A and increase of intracellular calcium, via the PLC␥/DAG/1,4,5-inositol triphosphate pathway, is observed in many cell types, little attention has been given to the interactions between both systems.…”
Section: Phosphatidylinositol 3-kinase I a (Pi3kmentioning
confidence: 99%